A novel colorimetric and ratiometric pH sensor with a notably large Stokes shift for sensing extremely alkaline solution. (June 2021) - Fang, Guiqian; Wang, Ran; Zhan, Dongxue; Chen, Gaofei; Huang, Yujun; Ma, Zihan; Yao, Qingqiang; Wu, Zhongyu
Abstract: In this work, a facile hemicyanine-naphthalene-based fluorescent sensor for colorimetric and ratiometric sensing of pH was constructed via a simple synthesis process. Significantly, sensor 3 showed a high sensitivity to extremely alkaline solution and had a notably large Stokes shift (145 nm). Its absorbance and fluorescence enhanced or quenched obviously in the pH range of 5.0–12.0, accompanying with colour change. In addition, the fluorescence intensity increased 727-fold (F440 /F710 ) when the pH was adjusted to 12, indicating that sensor 3 showed great potential in the detection of extremely alkaline solution. Highlights: A novel colorimetric and ratiometric pH sensor was constructed via a simple synthesis process. It shows a high sensitivity to pH in range of 5.0–12.0, especially in extremely alkaline solution. Sensor 3 has a notably large Stokes shift (≥145 nm). The fluorescence intensity of sensor 3 increased 727-fold (F440 /F710 ) when the pH was adjusted to 12.